Pengaruh Relaksasi Autogenik dengan Mendengarkan Musik Klasik terhadap Penurunan Tekanan Darah pada Lansia Hipertensi - Febriani, Aulia Putri; Wahyuni, Endang Sri (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Hypertension is one of the leading causes of death among degenerative diseases, leading to heart failure, stroke, and other complications in the elderly. Hypertension can be treated pharmacologically or non-pharmacologically. One non-pharmacological method that can be used is autogenic relaxation combined with listening to classical music. This study aims to determine the effect of autogenic relaxation combined with listening to classical music on reducing blood pressure in elderly hypertensive patients. Objectives: To determine the effect of autogenic relaxation combined with listening to classical music on reducing blood pressure in elderly hypertensive patients. Methods: This study was quantitative with a pre-experimental one-group pretest-posttest design. The study was conducted in Gunung Sinogo Hamlet, Ngargorejo Village, Ngemplak District, Boyolali Regency. The sampling technique used was purposive sampling. The intervention was conducted eight times over four weeks, each session lasting 20 minutes. The autogenic relaxation session was accompanied by classical music, Mozart's Piano Concerto No. 21, II. Data analysis used the Shapiro-Wilk test and paired sample t-test. Results: The results showed that the majority of respondents with hypertension were aged 60-74 years (81%), and the majority of respondents were female (81%). Furthermore, a decrease in systolic blood pressure of 16 mmHg and a decrease in diastolic blood pressure of 11.57 mmHg was found. The statistical test yielded a p-value <0.001, indicating a significant effect of autogenic relaxation through listening to classical music on lowering blood pressure. Conclusion: This study demonstrates a significant effect of autogenic relaxation through listening to classical music on lowering blood pressure in hypertensive patients. Keywords: Autogenic relaxation, Classical music, Hypertension, Elderly.